2018
DOI: 10.1038/s41418-018-0124-5
|View full text |Cite
|
Sign up to set email alerts
|

MPTP-driven NLRP3 inflammasome activation in microglia plays a central role in dopaminergic neurodegeneration

Abstract: Parkinson's disease (PD) is a progressive neurodegenerative disease characterized by the loss of dopaminergic neurons in the substantia nigra (SN) and the reduction of dopamine levels in the striatum. Although details of the molecular mechanisms underlying dopaminergic neuronal death in PD remain unclear, neuroinflammation is also considered a potent mediator in the pathogenesis and progression of PD. In the present study, we present evidences that microglial NLRP3 inflammasome activation is critical for dopam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
232
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 307 publications
(244 citation statements)
references
References 56 publications
10
232
2
Order By: Relevance
“…In addition, several other exogenous stimuli or environmental toxins have been found to be responsible for producing neuronal damage by disrupting mitochondrial and lysosomal function and by producing ROS and other proteinaceous insults in PD . Toxins that produce PD‐like effects in both cellular and animal models, such as 1‐methyl‐4‐phenylpyridinium (MPP + ), 1‐methyl‐4‐phenyl‐1,2,3,6‐tetrahydropyridine (MPTP), 6‐hydroxydopamine (6‐OHDA), and paraquat, have been shown to activate the NLRP3 inflammasome in many recent studies …”
Section: Nlrp3: Structure Activation and Function In Pdmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, several other exogenous stimuli or environmental toxins have been found to be responsible for producing neuronal damage by disrupting mitochondrial and lysosomal function and by producing ROS and other proteinaceous insults in PD . Toxins that produce PD‐like effects in both cellular and animal models, such as 1‐methyl‐4‐phenylpyridinium (MPP + ), 1‐methyl‐4‐phenyl‐1,2,3,6‐tetrahydropyridine (MPTP), 6‐hydroxydopamine (6‐OHDA), and paraquat, have been shown to activate the NLRP3 inflammasome in many recent studies …”
Section: Nlrp3: Structure Activation and Function In Pdmentioning
confidence: 99%
“…37 Toxins that produce PD-like effects in both cellular and animal models, such as 1-methyl-4-phenylpyridinium (MPP + ), 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP), 6-hydroxydopamine (6-OHDA), and paraquat, have been shown to activate the NLRP3 inflammasome in many recent studies. [38][39][40][41] On sensing particular stimuli, NLR proteins process a set of sequential signals to form the inflammasome. 42 The expression of pro-IL-1β and pro-IL-18 is triggered by the transcription factor nuclear factor kappa light chain enhancer of activated B cells (NF-κB).…”
Section: Nlrp3: Structure Activation and Function In Pdmentioning
confidence: 99%
“…In mice, activation of microglial NLRP3 inflammasome by misfolded α-synuclein causes the death of proximal dopaminergic neurons. [1,3,[8][9][10][11] The found TiO2 particles are coated with a protein-layer, constituting about 20 % of their mass. TiO2, shown to adsorb and orient peptides and polymers [27][28][29] could also adsorb α-synuclein or its precursor peptides.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the past 5 years have shown that a cause of the degeneration is inflammatory attack of dopaminergic neurons of the substantia nigra by microglia when their NLRP3 inflammasome is activated by phagocytized misfolded α-synuclein. [1][2][3][4][5][6][7][8][9][10][11][12] The misfolded β-sheet-rich α-synuclein aggregates in PD's hallmark Lewy bodies. If misfolded α-synuclein templates the misfolding of more synuclein, it constitutes a PD-propagating prion.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the role of metabolic species regulating the NLRP3inflammasome and neurodegeneration was recently evidenced by showing that the 25-hydroxycholesterol also activates the NLRP3-inflammasome pathway, promoting progressive neurodegeneration in X-linked adrenoleukodystrophy, a nervous disease with cerebral inflammatory demyelination (Jang et al, 2016). Moreover, the NLRP3 inflammasome pathway has been identified to contribute to PD (Fan et al, 2017;Gordon et al, 2018;Lee et al, 2018), AD and ALS (Heneka et al, 2013;Johann et al, 2015), HD (Glinsky, 2008), as well as to behavioral alterations in mice at later stages, such as anhedonia (Zhu et al, 2017), anxiety (Lei et al, 2017) and depression-like behavior (Pan et al, 2014;Su et al, 2017).…”
Section: Potential Role Of the Nod-like Receptor Protein 3 Inflammasomentioning
confidence: 99%